The nestling – waiting for adulthood? - Bartosz, Bogna; Lewandowska, Agata; Antczak, Iga (Department of Psychology, University of Wrocław, 2014)
Our article deals with the problem of ‘nestlings’ – young adults who postpone the moment of entering adulthood. A brief review of data and research results indicates that delays in undertaking developmental tasks typical of adulthood refer to a professional job, starting a family or a relationship, and gaining independence (not only financially). We discuss cultural, economic and psychological contexts of nestling, and attempt to answer the question whether waiting for adulthood is a global problem or a problem specific to only certain countries or just to Poland. It seems necessary to undertake research on this phenomenon. Nestling ought to be explored not only from the adult child’ perspective but from the parental perspective as well.
Keywords: cultural and social reasons; psychological reasons; adult children; parents of adult children; global problem; waiting for adulthood; explorative research; economic reasons